Isokinetic performance of knee extensor and flexor musculature in adolescent female handball players - Viçosa Bonetti, L.; Coulon Grisa, N.; Silveira Demeda, C.; Temp Finger, A. L.; De Marchi, T.; Saciloto Tadiello, G. (Archivos de medicina del deporte, 2018)
Background: Handball is a sport that requires an extensive variety of movements and has led to an increased incidence of ankle and knee injuries. Specifically, to knee joint, detection and reduction in muscular deficits can help prevent injuries and improve muscular performance. Isokinetic dynamometer is a highly effective and trustworthy assessment tool for such detections. Therefore, the objective of this study was to analyze muscular performance, and the differences between dominant and non-dominant limb of the knee extensors and flexors in adolescent handball athletes.